2013
DOI: 10.1037/a0033849
|View full text |Cite
|
Sign up to set email alerts
|

Converging to the lowest common denominator in physical health.

Abstract: This research demonstrates the impact of the lowest common denominator in physical activity: people's activity levels tend to converge to the lowest-performing members of their groups. This research adds to our understanding of the factors that determine when the behavior of others impacts our own behavior for the better-and the worse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The remaining article [28] reported outcomes discrepant with registered outcomes. The registry entry for this RCT specified the 3-month time point as primary.…”
Section: Objective 3 -Comparison Of Registered Primary Outcomes To Pumentioning
confidence: 77%
“…The remaining article [28] reported outcomes discrepant with registered outcomes. The registry entry for this RCT specified the 3-month time point as primary.…”
Section: Objective 3 -Comparison Of Registered Primary Outcomes To Pumentioning
confidence: 77%
“…48 Over the 6-month period, they found that the individual group had higher levels of activity but that activity among all groups steadily declined over time. Although John and Norton may have hoped that relative performance feedback would spur greater performance among the lower performers in each group, they found that in the group arms, activity tended to decline to the “least common denominator” as performance converged to the level of the lowest performer in the group.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have found that behavior declines when participants learn that they are performing better than others 6,10 or that social comparison feedback has little impact on those who are performing better than others. 11 To examine whether the impact of the social comparison feedback in the current study was due to the effects of being told that one was doing worse than others or the effects of being told one was doing better than others, or both, we repeated the analysis using days 2 through 12 of the intervention period, dropping the day variable and including instead a binary variable that indicated whether the participant's previous day performance was in the top or bottom half of the comparison distribution (for participants in the experimental condition, this corresponds to being told that they performed better or worse than average).…”
Section: Resultsmentioning
confidence: 99%
“…Our results found no ''boomerang'' effect of positive social comparison, as has been found in some previous studies. 6,10 This could have been due to a competition effect driven by the face-to-face nature of the interactions of the participants or perhaps by subtle injunctive walking norms, as injunctive norms have been found to eliminate the boomerang effect of positive social comparison. Further research will be needed to investigate these possibilities.…”
Section: Limitationsmentioning
confidence: 99%